The effect of spraying with yeast and supplementary irrigation on some morphological and productive traits of Organum vulgare (Latakia University Journal -Biological Sciences Series, 2025)
The research was conducted in Al-Aseiba in the Baniyas region, Tartous governorate, for the 2023 agricultural season with the aim of studying the effect of spraying with baker's yeast at concentrations of 0, 4 and 6 g/l and two treatments of supplementary irrigation (with or without supplementary irrigation) on some morphological and productive traits of Khalili thyme, such as traits (plant height (cm), number of branches/plant) and productivity (number of leaves/plant, fresh and dry plant weight (g)) of Khalili thyme. The experiment was conducted according to a randomized complete block design (R.C.B.D.) with three replicates for each treatment. The results showed that the treatment of spraying with baker's yeast and supplementary irrigation was significantly superior to the control treatment in all studied traits, as the treatment of spraying with baker's yeast at a concentration of 6 g/l gave the best values ​​for the trait of plant height, number of leaves , number of and branches, and fresh and dry weight. The treatment of spraying with baker's yeast with supplementary irrigation was also significantly superior to the rest of the studied treatments in all studied traits.